A Case Report of Silver-Russell Syndrome in Iran - Mahdian, Arezoo; Safari, Shiva; Sanagoo, Nazanin (Journal of Dental School, 2020)
Objectives Silver-Russell syndrome (SRS) is a rare genetic disorder which is typically characterized by prenatal and postnatal growth failure and asymmetry in the size of the two halves or other parts of the body. Herein, we report accurate diagnosis and management of a patient with SRS. Case Our patient was a 9-year-old boy with short stature and dysmorphic facial profile. The patient was diagnosed with SRS based on clinical and radiographic features such as short stature, triangular face, mandibular hypoplasia and clinodactyly. He was under growth hormone therapy since birth. The orthodontic treatment plan was space management for permanent teeth and growth modification to accelerate mandibular growth potential. Conclusion Early diagnosis and treatment are very important for SRS patients. Growth hormone therapy is often prescribed. It is necessary to persuade these patients to undergo early orthodontic intervention and comply with the follow-up protocol.